(untitled) (Educação e Pesquisa, 2003)
This work investigates from a philosophical perspective the concept of childhood in Plato, with an emphasis on the following dialogues: Alcibiades I, Gorgias, The Republic, and The Laws. Initially, we situate the issue of childhood within the wider scenario of Plato's political and philosophical project. We then propose four main features of the concept of childhood in Plato: a) as possibility (children can become anything in future); b) as inferiority (children - like women, foreigners and slaves - are inferior to the male adult citizen); c) as superfluousness (childhood is not necessary to the polis), and d) as matter of politics (the utopia is built from the education of children). It has not been our intention here to put Plato on trial. We have just sought to delimit an issue and a specific manner of tackling it with the aim of contributing to the analysis of the productivity of this perspective in the history of the philosophy of childhood and of Western education, as well as of current education theories and practices. At the same time, we have implicitly tried to offer elements to problematize a vision well established among historians of childhood - particularly after Philippe Ariès already classic Centuries of childhood: a social history of family life - according to which childhood would be a modern invention and would not have been "thought" as such by the ancients.